Correspondence regarding deed, Camden County, 1886 - State of Georgia (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1886)
Correspondence regarding deed, Camden County, 1886. Handwritten Correspondence on ruled stationery: Goodyear & Kay, Attorneys at Law, Brunswick, Ga., to the Clerk of the Superior Court of Camden County, Georgia from C.P. Goodyear regarding judgment in favor of E.A. Riley vs. J.B. Stafford. December 20, 1886. 1 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Camden County (Ga.); Deeds; Court records; Records and correspondence